Daily rhythms of glycerophospholipid synthesis in fibroblast cultures involve differential enzyme contributions - Acosta Rodríguez, Victoria América (2013)
Circadian clocks regulate the temporal organization of several biochemical processes including lipid metabolism and their disruption leads to severe metabolic disorders. Immortalized cell lines acting as circadian clocks display daily variations in [32P]-phospholipid labeling; however, the regulation of glycerophospholipid (GPL) synthesis by internal clocks remains unknown. Here we found that arrested NIH 3T3 cells synchronized with a 2 h-serum shock exhibited temporal oscillations in: a) the labeling of total [3H]- GPLs, with lowest levels around 28 and 56 h, and b) the activity of GPL-synthesizing and -remodeling enzymes such as phosphatidate phosphohydrolase 1 (PAP-1) and lysophospholipid acyltransferases (LPLAT) respectively, with antiphase profiles. In addition, we investigated the temporal regulation of phosphatidylcholine (PC) biosynthesis. PC is mainly synthesized through the Kennedy pathway with Choline Kinase (ChoK) and CTP:phosphocholine cytidylyltranferase (CCT) as key regulatory enzymes. We observed that the PC labeling exhibited daily changes with the lowest levels every ~28 h that were accompanied by brief increases in CCT activity and the oscillation in ChoK mRNA expression and activity. Results demonstrate that the metabolisms of GPLs and particularly of PC in synchronized fibroblasts are subject to a complex temporal control involving concerted changes in the expression and/or activities of specific synthesizing enzymes.